2012
DOI: 10.15218/zjms.2012.0025
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ligamentum flavum thickness correlation with demographic variables and disc degeneration in Erbil governorate population sample

Abstract: Background and objectives:This study aimed to investigate the correlation between the ligamentum flavum thickness and age, sex, body mass index and type of disc degeneration. Method: 126 consecutive patients were examined prospectively. The sample included all the patients who had an MRI examination after they presented to Rizgary teaching hospital complaining of lower back and/or leg pain. The LF thickness was measured by using lumbo-sacral spine MRI. Results: The mean thickness of LF was more at L4-L5 (right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…But this was not statistically significant (p>0.05). This result agreed with Akreyi et al 10 In Akreyi et al 10 , significant difference was found at L2-3 level, but this disc level was not included in the present study. In Sakamaki et al study 8 , no corelation was found between thickness of LF and decrease of the disc height (disc degeneration) in elderly patients.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…But this was not statistically significant (p>0.05). This result agreed with Akreyi et al 10 In Akreyi et al 10 , significant difference was found at L2-3 level, but this disc level was not included in the present study. In Sakamaki et al study 8 , no corelation was found between thickness of LF and decrease of the disc height (disc degeneration) in elderly patients.…”
supporting
confidence: 93%
“…Kolte et al 11 and Akreyi et al 10 found that the mean LF thickness was more at L4-5 followed by L5-S1 and L3-4 whearas in Sairyo et al 7 thickest LF was found at L4-5 level. In Abbas et al study 9 and Altinkaya et al study 6 , thickest LF was found at L4-5 followed by L3-4 and than L5-S1.They related this to the hypermobility of spine at these two levels i.e L4-5 and L3-4.…”
Section: Okuda Et Almentioning
confidence: 91%
See 2 more Smart Citations